Carbon and Nitrogen Acquisition in Shallow and Deep Holobionts of the Scleractinian Coral S. pistillata - Ezzat, Leïla; Fine, Maoz; Maguer, Jean-François; Grover, Renaud; Ferrier-Pagès, Christine (Frontiers in Marine Science, 2017)
Reef building corals can host different symbiont genotypes (clades), and form distinct holobionts in response to environmental changes. Studies on the functional significance of genetically different symbionts have focused on the thermal tolerance rather than on the nutritional significance. Here, we characterized the nitrogen and carbon assimilation rates, the allocation patterns of these nutrients within the symbiosis, and the trophic condition of two distinct holobionts of Stylophora pistillata: one associated with Symbiodinium clade A in shallow reefs and the other one associated with clade C in mesophotic reefs. The main findings are that: (1) clade C-symbionts have a competitive advantage for the acquisition of carbon at low irradiance compared to clade A-symbionts; (2) light is however the primary factor that determines the positive relationship between the amount of carbon fixed in photosynthesis by the symbionts and the amount of carbon translocated to the host; and (3) by contrast, the dominant Symbiodinium type preferentially determines a negative relationship between rates of coral feeding and nitrogen assimilation, although light still plays a relevant role in this relationship. Clade C-holobionts had indeed higher heterotrophic capacities, but lower inorganic nitrogen assimilation rates than clade A-holobionts, at all light levels. Broadly, our results show that the assimilation and translocation rates of inorganic carbon and nitrogen are clade and light-dependent. In addition, the capacity of S. pistillata to form mesophotic reefs in the Red Sea relies on its ability to select Symbiodinium clade C, as this symbiont type is more efficient to fix carbon at low light.